2002
DOI: 10.1046/j.1365-2796.2002.01057.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smokeless tobacco use on smoking in northern Sweden

Abstract: Abstract. Rodu B, Stegmayr B, Nasic S, Asplund K

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
84
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 13 publications
12
84
1
2
Order By: Relevance
“…ex-smokers become snuff dippers). 35,38 We detected no positive association regarding NHL and being overweight or obese. Impaired immune function, effects on cell proliferation and nutritional factors are some of the postulated putative biological mechanisms, but the ethological role of these factors have not been fully verified.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…ex-smokers become snuff dippers). 35,38 We detected no positive association regarding NHL and being overweight or obese. Impaired immune function, effects on cell proliferation and nutritional factors are some of the postulated putative biological mechanisms, but the ethological role of these factors have not been fully verified.…”
Section: Discussioncontrasting
confidence: 53%
“…[33][34] Tobacco in the form of Swedish moist oral snuff (snus) is today highly prevalent in the Swedish male population, and has been increasing during the past decades from 22% to 30%. 35 The proposal that usage of smokeless tobacco might lead to smoking behavior [36][37] has been of major concern, however some results suggest snuff dipping to be more closely related to cessation of smoking (i.e. ex-smokers become snuff dippers).…”
Section: Discussionmentioning
confidence: 99%
“…23 During the same period, the prevalence of smoking in men decreased from 23% to 14% in the group aged 25 to 64 years. 24 In women, the decline started later and it has been more modest (from 27% to 22%). 24 Thus, one reason for the different trends in incidence could be the different trends in smoking habits between men and women.…”
Section: Stegmayr Et Al Declining Mortality From Sah In Northern Swedmentioning
confidence: 99%
“…24 In women, the decline started later and it has been more modest (from 27% to 22%). 24 Thus, one reason for the different trends in incidence could be the different trends in smoking habits between men and women. However, calculation of the population-attributable risk (PAR) showed that the reduction in the prevalence in smoking men during 1986 to 1999 explains only a minor part of the reduction in incidence in men.…”
Section: Stegmayr Et Al Declining Mortality From Sah In Northern Swedmentioning
confidence: 99%
“…We identified 373 articles addressing multiple tobacco product use. Of these, twenty-five articles (Backinger et al, 2008;Bombard, Pederson, Nelson, & Malarcher, 2007;Bombard, Rock, Pederson, & Asman, 2008;Chao et al, 2002;Croucher, Islam, & Pau, 2007;Digard, Errington, Richter, & McAdam, 2009;Everett, Malarcher, Sharp, Husten, & Giovino, 2000;Galanti, Rosendahl, & Wickholm, 2008;Gilpin & Pierce, 2003;Horn, Gao, Dino, & Kamal-Bahl, 2000;Lando, Haddock, Klesges, Talcott, & Jensen, 1999;Mumford, Levy, Gitchell, & Blackman, 2005Post et al, 2005Post et al, , 2010Rigotti, Lee, & Wechsler, 2000;Rodu & Cole, 2009;Rodu, Stegmayr, Nasic, & Asplund, 2002;Skander & Larbaoui, 1989;Spangler et al, 1999Spangler et al, , 2001Tercyak & Audrain, 2002;Tomar, 2002;Wetter et al, 2002;Wickholm, Galanti, Soder, & Gilljam, 2003) reported prevalence data based upon the type and frequency of tobacco use (Supplementary Appendix A). Several different terms were used to describe the simultaneous use of two tobacco products, including "dual use" (Digard et al, 2009;Post et al, 2010;Rodu & Cole, 2009;Spangler et al, 1999Spangler et al, , 2001, "concurrent use" (Croucher et al, 2007;Mumford et al, 2005Mumford et al, , 2006Tomar, 2002), "combined use" (Rodu et al, 2002;Wickholm et al,...…”
Section: Introductionmentioning
confidence: 99%